Faktor Prediktif Efektifitas Edukasi Farmasis pada Masa Pandemi COVID-19 melalui Media Leaflet terhadap Kualitas Hidup Pasien Hipertensi di Puskesmas Sedayu 1 Bantul - Nurul Kusumawardani; Mirzaliana Mirzaliana; Wahyuningsih Wahyuningsih; Mahfud Mahfud (Universitas Muhammadiyah Surakarta, 2021)
Quality of life (QoL) assessment related to health is one of the therapeutic outcomes that can determine the goal of treatment. This study aims to determine the effectiveness of pharmacist education using leaflet media during the COVID-19 pandemic and its predictive factors for the quality of life of uncomplicated primary hypertension patients at Sedayu 1 Public Health Center, Bantul. The method used was quasi-experimental with pre-test and post-test with control group design. The sampling technique was purposive sampling in July-September 2020, until the end of the study, there were 90 respondents who were divided into control and treatment groups. The treatment given was in the form of education with leaflet media on the 1st day of the pretest and post-test evaluation on the 31st day. Instruments measuring the quality of life by WHOQoL-BREF. Statistical analysis of the basic characteristics of the respondents and the effectiveness of education were presented descriptively and were analyzed using the Wilcoxon and Mann-Whitney tests (α=95%, p-value0,050 statistically significant). Predictor factors of quality of life are known based on binary logistic regression modeling. The results of this study indicate that there is a significant effect of pharmacist education on quality of life in one of the psychological domains based on the mean value of the transformed score (p-value=0,003), as well as the overall domain in the control group compared to the intervention group (66.29±3.54 and 68.04±2.86., p-value=0.025), with a positive quality of life percentage of 46.70% and 53.30%, respectively. The main predictive factor that most influenced respondent low QoL during the COVID-19 pandemic is control blood pressure (odds ratio [OR]=2.75;95%CI = 1.12–6,87; p-value=0.030). This research shows that the role of the pharmacist is very important in improving the quality of life of people with hypertension, that it will have an impact on reducing hypertension morbidity and mortality, especially during the COVID-19 pandemic.